MENSTRUAL CYCLE AND FEMALE ATHLETIC PERFORMANCE: A SYSTEMATIC REVIEW - Monika Białowąs; Weronika Białowąs; Michał Maćkowski; Sandra Balon; Kacper Piotr Urban; Adam Śmietana; Piotr Szwed; Natalia Julia Sojka; Karolina Maria Dubiel; Jakub Jan Magnowski (International Journal of Innovative Technologies in Social Science, 2025)
This systematic review and meta-analysis aimed to investigate the effects of menstrual cycle phases on women’s physical performance. Data from 78 studies were analyzed, encompassing assessments of both aerobic capacity and muscular strength. The findings indicate that menstrual cycle phases exert only a minimal influence on physical performance, with small and clinically insignificant differences between phases. The most pronounced variation was observed between the early and late follicular phases, yet these differences did not reach clinical relevance. Network meta-analysis supported these outcomes, demonstrating minor fluctuations in performance across the menstrual cycle. The overall quality of evidence was rated as low, underscoring the need for further high-quality research. In conclusion, the influence of menstrual cycle phases on physical performance appears to be minimal, and training recommendations should be individualized, considering each woman’s specific physiological responses and needs. Methods: The review was based on an analysis of articles published in the PubMed, Scopus, and Web of Science databases between 2005 and 2025, using the following keywords: menstrual cycle, cycle phases, eumenorrhea, physical performance, endurance, muscle strength, VO₂max, lactate threshold, hormonal contraception, estrogens, progesterone, recovery, fatigue, RPE, training, women’s sport. Only peer-reviewed, full-text articles published in English were included. The selection encompassed original research studies, systematic reviews, meta-analyses, and expert consensus statements, with a particular focus on studies evaluating the effects of menstrual cycle phases on physical performance, strength and power parameters, as well as recovery and fatigue perception indicators. The analysis integrated physiological, hormonal, and metabolic mechanisms with findings from clinical and sports performance studies to provide a comprehensive understanding of the relationship between menstrual cycle phases and female exercise capacity. Results: Analyses of systematic reviews and meta-analyses indicate that the influence of menstrual cycle phases on physical performance is small but detectable in certain measures. Meta-analyses have shown slight advantages in selected strength metrics (e.g., isometric and isokinetic strength) during the late follicular and ovulatory phases, although the observed effects are small and heterogeneous. Most studies do not confirm significant differences in VO₂max or time to exhaustion between menstrual phases. Experimental data suggest a protective effect of estradiol on muscle damage and a faster recovery following eccentric exercise. Biomechanical analyses and review studies also point to increased joint laxity around ovulation, which may partly explain the higher risk of anterior cruciate ligament (ACL) injuries observed during this period, although the overall quality of evidence remains limited. Conclusions: A review of the current literature indicates that the phases of the menstrual cycle may modulate women’s maximal strength. Isometric and isokinetic performance measures tend to exhibit a slight improvement during the late follicular phase and ovulation; however, these effects are generally small and often lack clinical significance. In terms of aerobic capacity (VO₂max and time to exhaustion), the evidence does not demonstrate consistent or substantial variations across menstrual cycle phases. Muscle recovery and susceptibility to damage appear to be more favorable during periods of elevated estrogen concentrations. Conversely, biomechanical parameters, including ligament laxity and neuromuscular control, may fluctuate throughout the cycle, potentially increasing injury risk near ovulation, although empirical support for this association remains limited.